An introduction to distance education : understanding teaching and learning in a new era - Cleveland-Innes, Martha, 1956-; Garrison, D. R. (D. Randy), 1945- (New York, NY : Routledge, 2021)
"An Introduction to Distance Education is a comprehensive look at the field of distance education, outlining current theories, practices, and goals that are essential to effective design, delivery, and navigation. As an alternative pedagogical approach, distance education is posited to meet the evolving demands for access, affordability, and quality in higher education. This fully revised and updated second edition reviews the history of distance education while addressing its current influence on the education sector. Utilizing a student-guided approach, each chapter offers pedagogical features to engage and support the teaching and learning process, including: questions for reflection, review and discussion: students can use these questions as triggers for further thoughts related to the topic. Instructors can use these questions for classroom and online discussion key quotations: strategically placed throughout the text, these points act as a springboard for further reflection and classroom discussion concept definitions: central concepts discussed in the text are defined or students at the end of each chapter. Driven by seminal contributors who are researching and shaping our understanding and practice of distance education today, An Introduction to Distance Education offers a solid foundation from which to explore and develop new approaches to designing and implementing online courses. Dr. Martha Cleveland-Innes is Professor and Program Director in Graduate Education Programs"--
Foreword / Richard A. Schwier -- Teaching and learning in distance education : continue a new era / M.F. Cleveland-Innes -- From independence to collaboration : a personal retrospective on distance education / D.R. Garrison -- Formal and informal paths of lifelong learning : hybrid distance educational settings for the digital era / J. Jaldemark -- Failures of open and distance education's successes / H. Kanuka -- Teaching and learning in post-industrial distance education / K. Swan -- Into the breach : the emerging landscape in online learning / P. Ice and M. Layne -- Blended learning revisited / N. Vaughan -- Repositioning and re-purposing distance education for the future / T. Evans and B. Pauling -- Leadership in a new era of distance higher education / A. Sangrà and M.F. Cleveland-Innes -- From distance education to blended learning : leading pedagogical change / K. Matheos and M.F. Cleveland-Innes -- Teaching, learning, and beyond / M.F. Cleveland-Innes and D.R. Garrison.
Includes bibliographical references and index.
Keywords: Distance education